Copper, Chromium and Manganese in Some Fishes of Kali Estuary, Karwar - M.P., Veer; U.G., Bhat; H., Shanmukhappa (Fishery Technology, 2025)
Copper, chromium and manganese concentrations in the gill, muscle and whole body samples of four estuarine fishes, namely, Mugil cephalus, Sillago sihama, Leiognathus brevirostris and Gerromorpha setifer were determined during the period July- November, 1989. Concentrations of these metals in different body parts varied from species to species. The three trace metals in M. cephalus, S. sihama and L. brevirostris in whole body were in the order Mn > Cr >Cu whereas in G.setifer the abundance was in the order Cr >Cu >Mn. Significant correlation was observed between concentration of metals in gills and whole body in all species except M. cephalus. Considering the trace metals concentration in relation to wet weight, all the metals are within safety limits in edible part.